The Eyes Have It: Eyelid Swelling and Rash in a 79-year-old Woman With Macular Degeneration. (April 2018) - Kleris, Renee S.; Keswani, Anjeni; Lugar, Patricia
Introduction: A 79-year-old woman with macular degeneration was referred to the Allergy/Immunology clinic for the evaluation of a potential allergy to anti-vascular endothelial growth factor (anti-VEGF) treatments. The patient developed urticaria and eyelid swelling immediately following a retinal injection of aflibercept, which she had previously tolerated. She previously had allergic reactions following ranibizumab and bevacizumab injections. Injections of anti-VEGF treatments were discontinued given concern for allergy with progression of the patient's disease. Objective: To assess the culprit medication(s) responsible for hypersensitivity reactions following anti-VEGF injections for macular degeneration. Methods: Medication records were reviewed for each retinal injection. All medications used in each procedure, including the anti-VEGF therapy (aflibercept), topical anesthetics (tetracaine and proparacaine hydrochloride), and antiseptic (povidine), were evaluated with skin testing. She was additionally tested for alternative anti-VEGF therapies (ranibizumab and bevacizumab) as she was thought to have allergies to these agents by prior history. A test dose challenge was completed for aflibercept, ranibizumab, and bevacizumab. Results: Skin prick and intradermal testing were negative to aflibercept, ranibizumab, bevacizumab, and povidine. Intradermal testing was positive to tetracaine and proparacaine hydrochloride. The patient passed test dose challenges to aflibercept, ranibizumab, and bevacizumab. Due to her positive hypersensitivity testing to 2 ester anesthetics, the patient underwent skin prick and intradermal testing to the amide anesthetic, lidocaine. This was negative and the patient tolerated a graded challenge to lidocaine. She was deemed to have an immunoglobulin E (IgE)-mediated hypersensitivity to ester-type local anesthetics. She successfully resumed anti-VEGF therapy with an amide local anesthetic. Conclusions: The reason for this consult was the concern for hypersensitivity to a biologic anti-VEGF medication. The culprit allergen, the local anesthetic, could have been overlooked without an assessment of all medications used during the procedure. This case highlights the importance of a thorough allergy evaluation of all medications used during procedures to determine the causative agent. Chief Complaint: Eyelid swelling and rash after ophthalmic procedures for macular degeneration.